Erwinia chrysanthemi EC16 produces a second set of plant-inducible pectate lyase isozymes - Kelemu, Segenet; Collmer, A (1993)
The enterobacterium Erwinia chrysanthemi causes soft-rot diseases involving extensive tissue maceration in a wide variety of plants and secretes multiple pectic enzymes that degrade plant cell walls and middle lamellae. An E. chrysanthemi mutant with directed deletions or insertions in genes pehX, pelX, pelA, pelB, pelC, and pelE, which encode exo-poly-?-D-galacturonosidase, exopolygalacturonate lyase, and four isozymes of pectate lyase, respectively, was constructed by the marker exchange of a cloned pehX